Buried interface defects 2-bromo-1-ethylpyridinium tetrafluoroborate passivates tin oxide layer for high-performance planar perovskite solar cells - Mariyappan, Thambidurai (2024)
The electron transport layer/perovskite interfaces play a crucial role in facilitating efficient charge transfer and minimizing recombination losses, which are key factors for achieving high power conversion efficiency (PCE) in perovskite solar cells (PSCs). Herein, a novel ionic liquid called 2-bromo-1-ethylpyridinium tetrafluoroborate (BEPBF4) is added between tin oxide (SnO2) and perovskite layers to improve the photovoltaic performance of PSCs. The BEPBF4 interface modification not only reduces the defect density, increases the crystallinity, and aligns the energy bands at the interface but also shortens the lifetime of the charge carriers, resulting in improved PCE and stability. Consequently, the device modified with BEPBF4 achieved a PCE of 20.14% and retained 94% of the initial PCE without encapsulation, in contrast to the control device (18.41%), which retained only 82% of the initial PCE after 1000 h of storage at ambient conditions. In addition, the BEPBF4-PSCs exhibited significantly better thermal stability, retaining 64% of the initial PCE after 400 h of continuous thermal aging at 85 °C, compared to only 31% for the unencapsulated pristine device.